How Economic Theories Can Help Computers Beat the Heat. - Wenisch, Thomas F. (Communications of the ACM, 2019)
A preview is presented for an essay in the issue on computational sprinting, or the concept of running a computer to the point of overheating for a short period of time to get a quick period of performance.